COST CUTTING MEASURES AT COOPERATIVE BANKS IN GERMANY AS A RESULT OF DIGITALIZATION AND THEIR CONSEQUENCES - GIEBE, Carsten; Schulz, Kevin (Journal of Economic Development, Environment and People, 2021)
The banking market in Germany is facing big challenges due to digitalization. The digital transformation is significantly influenced by technological progress and the low-interest phase. The article deals with the group of cooperative banks, which consists of many individual cooperative credit institutions. Cooperative banks are credit institutions whose objective, according to their statutes, is the economic promotion of their members through joint business operations. The traditional classical business model is traditionally based on personal customer contact. More mergers are to be expected in the banking sector in the coming years. The process of branch closures and staff reductions is also inevitable. Although the role of branches is up for discussion, they are increasingly falling victim to increased cost pressures. These changes have an impact on many aspects of how bank customers demand, evaluate and ultimately purchase financial services. In recent years, it has become clear that banks lack a clear strategy. The aim should be that the strategy does not focus exclusively on cost cutting, such as branch closures and staff reductions. The main purpose of this research is to investigate whether these cost cutting measures in cooperative banks are operationally justified in relation to the available operating profit, cost income ratio and return on equity. The results of this article may be relevant for researchers dealing with the Digital Transformation in the banking sector in Germany.